2006
DOI: 10.1186/1471-2407-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of apoptosis proteins in human cervical cancer

Abstract: Background: It has been shown that IAPs, in particular XIAP, survivin and c-IAP1, are overexpressed in several malignancies. In the present study we investigate the expression of c-IAP1, c-IAP2, XIAP and survivin and its isoforms in cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
(29 reference statements)
2
34
0
Order By: Relevance
“…Because survivin is not present in healthy tissue but is expressed in neoplastic tissue and involved in tumor progression, it has been investigated as a potential target for antineoplastic therapy. 14 In the present study, moderate to strong survivin expression was detected in 70% of the samples in the CIN-2 group, 66.7% of the samples in the CIN-3 group, and 74.6% of the samples in the ICC group, which is in agreement with the findings of Espinosa et al 15 Specific studies of telomerase in cervical cancer have suggested that telomerase activity may be a definitive and reliable test for malignancy. The detection of human telomerase RNA seems to be in good agreement with the levels of telomerase activity detected by telomeric repeat amplification protocols.…”
Section: Discussionsupporting
confidence: 95%
“…Because survivin is not present in healthy tissue but is expressed in neoplastic tissue and involved in tumor progression, it has been investigated as a potential target for antineoplastic therapy. 14 In the present study, moderate to strong survivin expression was detected in 70% of the samples in the CIN-2 group, 66.7% of the samples in the CIN-3 group, and 74.6% of the samples in the ICC group, which is in agreement with the findings of Espinosa et al 15 Specific studies of telomerase in cervical cancer have suggested that telomerase activity may be a definitive and reliable test for malignancy. The detection of human telomerase RNA seems to be in good agreement with the levels of telomerase activity detected by telomeric repeat amplification protocols.…”
Section: Discussionsupporting
confidence: 95%
“…It is conceivable that the overexpression of IAPs may be linked with tumor prognosis and drug resistance to chemotherapy (10). Among studies that associate IAPs with the clinical outcome, XIAP expression has been shown to have an adverse prognostic significance for patients with lung cancer (11), mesothelioma (12), and myeloid leukemias (13), but not for cervical cancer (14). In chemoresistance studies, expressions of XIAP and cIAP2 in pancreatic and prostate cancer have been shown to be associated with resistance to cisplatin and other anticancer drugs (15)(16)(17).…”
mentioning
confidence: 99%
“…AIF is a caspase-independent apoptosis effector that can be released from the mitochondria into the cytosol (27)(28)(29), and is believed to be involved in caspase-independent cell death (17,18). Correspondingly, our Western blot analysis revealed that treatment of HA22T cells with 0, 50, 100, 150, 200 and 250 µg/ml YBBEs for 24 h resulted in increased AIF production (Fig.…”
Section: Discussionmentioning
confidence: 52%